2018
DOI: 10.5114/fmpcr.2018.79348
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting stunting among under-five children in Bangladesh

Abstract: Factors affecting stunting among children under five years of age in BangladeshAshis TAlukder A-F , shAhArior rAhmAn rAzu A, D-F , md. zobAyer hossAin A, D-F orCid id: 0000-0002-5031-1128 khulna university, bangladeshBackground. Stunting is a major contributor to child morbidity and mortality in developing countries. Knowledge about the risk factors of stunting among children under five years of age is important for devising nutritional intervention programs and strategies.Objectives. This study attempts to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
(48 reference statements)
3
13
0
9
Order By: Relevance
“…In line with the results of research in Malawi, findings in India, Bangladesh, and Ethiopia also received the same thing. Women's education can reduce child stunting [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the results of research in Malawi, findings in India, Bangladesh, and Ethiopia also received the same thing. Women's education can reduce child stunting [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, stunting remains one of the major public health problems among children under 5 years of age [ 1 ]. It is an indicator of malnutrition in early childhood and is strongly associated with numerous short-term and long-term conditions [ 2 , 3 ]. It is the best of overall indicator of children’s well-being and an accurate reflection of social inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…Child marriage is also suspected to cause anthropometric failure or anthropometric failure such as stunting, wasting, and underweight because women who marry young are more likely to have poor reproductive health status [3,15]. This study found that there was a tendency to decrease the incidence of stunting in Gunungkidul Regency after the enactment of the PPUA Regulation.…”
Section: Discussionmentioning
confidence: 80%